AKUISISI PERTAHANAN DAN EKSPOR SENJATA PASCA REVISI UU INDUSTRI PERTAHANAN DALAM OMNIBUS LAW SERTA POTENSI DAN KERAWANANNYA BAGI EKONOMI PERTAHANAN - Muhammad Rizki Arhan; Djoko Andreas Navalino; Yusuf Ali (JURNAL CAFETARIA, 2022)
One of the laws that were revised in the Omnibus Law of the Job Creation Law which was passed on October 5, 2020, is Law number 16 of 2012 concerning the Defense Industry. One of the points amended in the Act is the permitting of Private-Owned Enterprises (BUMS) as Lead Integrators for the Defense Industry. This revision indicates that the Defense Industry in Indonesia will be directed to a free market. This study aims to analyze defense acquisitions and weapons exports after the revision of the Defense Industry Law and the potential threats that can be posted through the revision of the Law. This study was structured using qualitative methods, research data obtained through observations, interviews, and review of documents that are considered relevant. The results of the study show (1) that there have been several positive trends since the Omnibus Law was ratified, both in terms of the amount of production or the number of Defense Industry, which in the future are expected to increase defense acquisitions through domestic production; (2) the trend of Indonesia's arms exports after the revision of the Defense Industry Law cannot be measured objectively because almost all economic activities are affected by the Covid-19 Pandemic, including the Defense Industry; (3) investment freedom through the revision of the Defense Industry Law does open up the potential for business competition in the domestic defense industry, but threats can arise if the existing liberalization is not regulated with certain limits that are adjusted to existing norms.